Trans-sialidase from Trypanosoma cruzi enhances the adhesion properties and fibronectin-driven migration of thymocytes - Nardy, Ana Flávia F.R. (2013)
In experimental Trypanosoma cruzi infections, severe thymic atrophy leads to release of activated CD4+CD8+ double-positive (DP) T cells to the periphery. In humans, activated DP T cells are found in the blood in association with severe cardiac forms of human chronic Chagas disease. The mechanisms underlying the premature thymocyte release during the chagasic thymic atrophy remain elusive. We tested whether the migratory properties of intrathymic thymocytes are modulated by the parasite trans-sialidase (TS). We found that TS affected the dynamics of thymocytes undergoing intrathymic maturation, and these changes were accompanied by an increase in the number of recent DP thymic emigrants in the peripheral lymphoid organs. We demonstrated that increased percentages of blood DP T cell subsets were associated with augmented antibody titers against TS in chagasic patients with chronic cardiomyopathy. In vitro studies showed that TS was able to activate the MAPK pathway and actin filament mobilization in thymocytes. These effects were correlated with its ability to modulate the adhesion of thymocytes to thymic epithelial cells and their migration toward extracellular matrix. These findings point to effects of TS that could influence the escape of immature thymocytes in Chagas disease.